2018
DOI: 10.7161/omuanajas.394923
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of social networks between organic and conventional hazelnut producers in Samsun

Abstract: This study was carried out to reveal the sources of communication and social network of organic and conventional hazelnut producers in Samsun province. The primary and basic material of the study is the data obtained from the surveys, interviews and observations of the organic and conventional hazelnut producers in Çamlıca, Yüksekyayla villages and Ağcagüney town. Both producer groups were compared in terms of their social networks and communication channels especially on the use of different fertilizers by ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The study determined that the family size of the paddy farmers consisted of an average of 4.7 people and did not differ according to the innovativeness groups ( p > 0.05). In previous studies (Aydoğan & Demiryürek, 2018; Demiryürek, 2010; Rogers, 1963), the family size of the farmers in the high innovativeness group was larger than the ones in the low innovativeness group. The research findings in this study differed from the findings of previous studies.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…The study determined that the family size of the paddy farmers consisted of an average of 4.7 people and did not differ according to the innovativeness groups ( p > 0.05). In previous studies (Aydoğan & Demiryürek, 2018; Demiryürek, 2010; Rogers, 1963), the family size of the farmers in the high innovativeness group was larger than the ones in the low innovativeness group. The research findings in this study differed from the findings of previous studies.…”
Section: Resultsmentioning
confidence: 79%
“…Abacı and Demiryürek (2019) argued that farmers had heard that an agricultural innovation adopted by other farmers brought success and that their observations of this activity would change their attitude over time. In addition, Aydoğan and Demiryürek (2018) stated that farmers' information sources were generally composed of informal sources and affected each other's attitudes. It could be concluded that the farmers influenced each other on environmental awareness and, consequently, their behavior toward the environment was similar.…”
Section: Resultsmentioning
confidence: 99%
“…Information networks can also facilitate the adoption of organic fertilizer and biopesticides by farmers [24,25] . Social networks are important for farmers to obtain information, and whether farmers adopt technologies is often influenced by the behavior of farmers running large-scale farms, cooperative status, social customs and the behavior of village cadres [23,26,27] .…”
Section: Technical Environment Characteristicsmentioning
confidence: 99%